Analyzing Storytelling In TESOL Interview Research. Issue 2 (26th May 2014) - Kasper, Gabriele; Prior, Matthew T.
<x xml:space="preserve">Abstract</x> Autobiographic research interviews have become an accepted and valued method of qualitative inquiry in TESOL and applied linguistics more broadly. In recent discussions surrounding the epistemological treatment of autobiographic stories, TESOL researchers have increasingly called for more attention to the ways in which stories are embedded in interaction and thus are bound up with the social contexts of their production. This paper advances these efforts by demonstrating an empirically grounded approach to storytelling as interaction. Drawing on the research tradition on storytelling in conversation analysis, the article offers a sample analysis of a story produced in an L2 English interview with an adult immigrant in the United States. By engaging sequential conversation analysis, membership categorization analysis, and occasioned semantics, it examines the interactional practices through which the storyteller and story recipient launch, produce, and end the telling of a story that furthers the purpose of the autobiographic interview. By following closely the participants' coordinated actions as they unfold in time, we trace how the parties accomplish the storytelling as an intelligible and meaningful activity through sequence organization and turn design. We conclude with recommendations for extending storytelling research in TESOL to meet the evolving needs and interests of the field.